Structural budget balances in oil-rich countries: The cases of Azerbaijan, Kazakhstan, and Russia - Vugar Ahmadov; Ulvi Sarkarli; Ramiz Rahmanov (Graduate Institute of International and Development Studies, 2018)
This study aims to analyse the discretionary fiscal policy of Azerbaijan, Kazakhstan, and Russia for the period 2003-2015 using the structural budget balance (SBB). The SBB considers the permanent component of oil revenue and therefore clearly defines the discretionary fiscal position and the aggregate demand effect of fiscal policy. The SBBs in Azerbaijan and Russia experience a deficit for most of the analysed period. A moderate SBB surplus is observed in Kazakhstan. The estimated SBBs also demonstrate that fiscal policies tend to be mainly procyclical in Kazakhstan and Russia. Azerbaijan conducted a counter-cyclical fiscal policy for half of the investigated period. Moreover, governments placed more importance on economic stabilization in 2009 due to the global financial crisis.
Keywords: E62; H60; 330; fiscal policy; structural budget balance; oil-rich countries; Azerbaijan; Kazakhstan; Russia